Evaluation of the anti‐tumour activity of Coriolus versicolor polysaccharopeptide (I'm‐Yunity) alone or in combination with doxorubicin for canine splenic hemangiosarcoma. (25th April 2022) - Gedney, Allison; Salah, Pascale; Mahoney, Jennifer A.; Krick, Erika; Martins, Reenie; Scavello, Heather; Lenz, Jennifer A.; Atherton, Matthew J.
Abstract: Canine splenic hemangiosarcoma (HSA) is an aggressive tumour of vascular endothelium that carries a grave prognosis following standard of care treatment with surgery and doxorubicin. A previous pilot study revealed potential anti‐tumour activity of I'm‐Yunity polysaccharopeptide (PSP) for canine HSA. The aim of this prospective study was to assess patient outcome when treated with PSP alone or in combination with doxorubicin post‐splenectomy compared to patients treated with surgery and doxorubicin that received a placebo in place of PSP. Dogs undergoing splenectomy for splenic HSA were eligible. Following splenectomy, owners were offered treatment with PSP alone or adjuvant doxorubicin chemotherapy (unblinded). Patients with owners that selected to proceed with doxorubicin chemotherapy were blindly randomized to receive placebo or PSP. Dogs were evaluated weekly for 15 weeks, then scheduled for monthly visits until death. One hundred and one dogs were included in the final analysis: 51 PSP alone, 25 doxorubicin/placebo, and 25 combination PSP/doxorubicin. On multivariate analysis, dogs treated with single agent PSP, female dogs, decreased haematocrit at diagnosis, and stage III disease were negatively significantly associated with outcome; however, an interaction between treatment group and sex was documented. Gender‐specific outcomes revealed no significant difference in survival between treatment groups for male dogs, but female dogs treated with PSP alone had significantly reduced survival compared to females receiving doxorubicin/placebo (HR 0.21; p = .004). Anaemia (HR 5.28; p < .001) and stage III disease (HR 2.9; p = .014) remained negatively associated with survival when controlling for sex and treatment group. The addition of PSP to doxorubicin post‐splenectomy did not improve survival in dogs with splenic HSA.